The effect of GnRH on pregnancy rates in estrus-synchronized beef heifers - M. Ferguson; L. Corah (Kansas Agricultural Experiment Station Research Reports, 1986)
Injecting 100 mcg of GnRH into cycling heifers at artificial insemination following estrus synchronization with either prostaglandin or Syncro-Mate-B® did not improve first service conception rate. However, GnRH improved first service conception in Syncro-Mate-B®-treated heifers that did not exhibit estrus prior to breeding and were bred by appointment.
Keywords: Cattlemen' s Day; 1986; Kansas Agricultural Experiment Station contribution; no. 86-320-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 494; Beef; GnRH; Pregnancy rates; Estrus-synchronized